Etio-pathogenesis and epidemiological features in asbest exposure and malignant mesothelioma: The role of tumor suppressor genes: Review - Tu?, Tuncer; Tu?, Esra (Turkiye Klinikleri, 2005)
Malignant pleural mesothelioma (MPM) and lung cancer, which is almost always lethal within a short period, presents with permanent lung parenchymal structural dysfunction due to inhalation of asbestos dust, which is an inorganic and fibrous mineral. Throughout the world, the frequency of MPM and asbestosis after dust inhalation by workers or their relatives working in industrial areas has gradually increased. In addition, in some residential districts with known asbestos content in soil, MPM may result from inhalation of dust spreading into the near atmosphere from white soil containing asbestos used as building material. Asbestos contamination as a result of environment or industry exposure increases the frequency of MPM in excess of 20 times of that of the normal population. In cases with MPM resulting from the effects of asbestos exposure, it has been reported that asbestos produces genotoxic effects. In molecular cytogenetic studies recently performed with limited patient numbers, it was also reported that in MPM cases there may be inactivation or allelic loss at the probable TSGs in this regions with 1p, 3p, 6q, 9p, 13q, 14q, 15q and 22q micro-deletions. In this report, data from recent literature regarding the etio-pathogenesis and epidemiological characters of asbestos exposure and MPM, as well as their relationship to tumor suppressor genes, is reviewed. Copyright © 2005 by Türkiye Klinikleri.
Asbest maruziyeti ve malign mezotelyoma'da etiyopatogenez ve epidemiyolojik özellikler; tümör supresör gen i?lişkileri
Keywords: Asbestosis; Etiology; Mesothelioma; Mutagenicity tests; Pleura